Virtual gardening: Identifying problems and potential directions for 'ecological awareness' through soil management and plant recognition gaming. Issue 2 (1st July 2020) - Lelièvre, Edwige; Rubino, Giovanni; Summerley, Rory; Phillips, Tim
Games are increasingly proven to be effective learning tools through a multitude of methodologies and approaches and this is no different for issues relating to the environment and the place of humans within it. We collaborated with the Eden Project to create a mobile game addressing some concerns on the ecological awareness of visitors that they raised with us: a mobile garden management game with a plant recognition technology. Such a project proved a valuable opportunity to understand how a game for smart devices might promote short-term ecological awareness for a general audience. Using a research creation methodology, we analyse, document and run a limited empirical study through user experience testing on players to investigate if the game had an effect on their ecological awareness.